A Production & operation management study on Virata Button Corporation - Calayag, Laura N. (College of Engineering, 1999)
Virata Button Corporation is one of the pioneers in the button-making industry. It specializes in the manufacturing of buttons made from sea shells, coconut shells and plastic resins. Its plant is located along 184 Canero Heights Susno Road Novaliches, Quezon City. The project study will be focusing on two of the company's major products, shell and polyester buttons. Three major problem areas were identified both by the study group and by the management. These were: (1) inventory system; (2) inefficient layout; and (3) inventory management. A technique in forecasting for the company's sales was provided. The forecast computed from this technique was used in determining the optimal order quantity and reorder point. A new plant layout was proposed for the plant, taking into consideration its plans for expansion. The new layout minimized the distance traveled and improved the physical condition of the plant, in effect, improving the working conditions of the workers. For better inventory management, labels and forms were designed to help make tracking down of inventory items an easy task.